Vedangadipti : collected works of K.N.M. Divakaran Namputiri - Namboothiri, Narayanan (Publication Division, 2013)
Collection of three works on Vedic and Sanskrit phonetics and biography of Sankaracarya by Sanskrit author from Kerala.